New Continuous Process for the Production of Lipopeptide Biosurfactants in Foam Overflowing Bioreactor - Guez, Jean-Sébastien; Vassaux, Antoine; Larroche, Christian; Jacques, Philippe; Coutte, François (Frontiers in Bioengineering and Biotechnology, 2021)
In this work, an original culture process in bioreactor named overflowing continuous culture (O-CC) was developed to produce and recover continuously mycosubtilin, a lipopeptide antifungal biosurfactant of major interest. The lipopeptide production was first investigated in shake conical flasks in different culture media (ACS, DSM and Landy), followed by a pH conditions optimization using MOPS and MES buffered media. A simple theoretical modeling of the biomass evolution combined with an experimental set-up was then proposed for O-CC processed in stirred tank reactor at laboratory scale. Seven O-CC experiments were done in modified Landy medium at the optimized pH 6.5 by applying dilution rates comprised between 0.05 and 0.1 h-1. The O-CC allowed the continuous recovery of the mycosubtilin contained in the foam overflowing out of the reactor, achieving a remarkable in-situ product removal superior to 99%. The biomass concentration in the overflowing foam was found to be two-fold lower than the biomass concentration in the reactor, relating advantageously this process to a continuous one with biomass feedback. To evaluate its performances regarding the type of lipopeptide produced, the O-CC process was either tested with strain BBG116, a mycosubtilin constitutive overproducing strain that also produces surfactin, and strain BBG125, it’s derivative strain obtained by deleting surfactin synthetase operon. At a dilution rate of 0.1 h-1, specific productivity of 1.18 mg of mycosubtilin.g-1(DW).h-1 was reached. Compared to others previously described bioprocesses using almost similar culture conditions and strains, the O-CC one allowed an increase of the mycosubtilin production rate by 2.06-fold.